2019
DOI: 10.1038/s41375-019-0487-8
|View full text |Cite
|
Sign up to set email alerts
|

Second cancer in Philadelphia negative myeloproliferative neoplasms (MPN-K). A nested case-control study

Abstract: We conducted a large international nested case-control study including 1,881 patients with Philadelphia-negative myeloproliferative neoplasms (MPN). Cases (n=647) were patients with second cancer (SC: carcinoma, non-melanoma skin cancer, hematological second cancer and melanoma) and controls (n=1,234) were patients without SC, matched with cases for sex, age at MPN diagnosis, date of MPN diagnosis and MPN disease duration. The aim was to evaluate the risk of SC after exposure to cytoreductive drugs. Patients e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 28 publications
5
89
2
Order By: Relevance
“…Overall, these observations may indicate that ruxolitinib‐induced toxicity is not predictive of inferior survival, as noted previously for anemia during ruxolitinib therapy. In addition, these findings highlight the importance of strictly monitoring ruxolitinib‐exposed patients in oncologic practice . However, despite the absence of statistical significance, the difference in median survival between patients who lacked or lost a spleen response and those who had ruxolitinib‐related adverse events may be clinically relevant (approximately 30 vs 13.2 months) and may have been caused in part by the lower likelihood of receiving further treatments in patients who discontinued ruxolitinib because of cytopenias or infections.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Overall, these observations may indicate that ruxolitinib‐induced toxicity is not predictive of inferior survival, as noted previously for anemia during ruxolitinib therapy. In addition, these findings highlight the importance of strictly monitoring ruxolitinib‐exposed patients in oncologic practice . However, despite the absence of statistical significance, the difference in median survival between patients who lacked or lost a spleen response and those who had ruxolitinib‐related adverse events may be clinically relevant (approximately 30 vs 13.2 months) and may have been caused in part by the lower likelihood of receiving further treatments in patients who discontinued ruxolitinib because of cytopenias or infections.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, these findings highlight the importance of strictly monitoring ruxolitinib-exposed patients in oncologic practice. 34,35 However, despite the absence of statistical significance, the difference in median survival between patients who lacked or lost a spleen response and those who had ruxolitinib-related adverse events may be clinically relevant (approximately 30 vs 13.2 months) and may have been caused in part by the lower likelihood of receiving further treatments in patients who discontinued ruxolitinib because of cytopenias or infections. From a clinical point of view, the latter patients are certainly the most vulnerable, with extremely limited therapeutic possibilities after ruxolitinib, and thus should require special attention and research.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these incident events, recent studies consistently reported that MPN patients are also prone to an increased risk of developing second cancers (SC). 7 In the present study, we re-examined this large database with the following two purposes: (a) to evaluate the prognosis of MPN patients with SC and (b) to establish whether cytoreductive and antiplatelet therapies have any impact on the survival of such patients. 6 We recently published the results from a nested case-control study with 647 MPN patients with SC and 1234 matched controls (MPN patients without SC) recruited from European LeukemiaNet (ELN) centers and reported that the exposure to cytoreductive drugs, such as hydroxyurea and ruxolitinib, increases the occurrence of nonmelanoma skin cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, the European Leukemia Net conducted a large international nested case‐control study, including 1881 patients with MPN with the aim to evaluate the risk of second cancer after exposure to cytoreductive drugs. Of note, in this study, hydroxyurea, ruxolitinib, and drug combination did not show an excess risk of hematological second cancer and carcinoma compared with unexposed patients . On the other hand, all of these drugs were associated with an increased risk of nonmelanoma skin cancer.…”
Section: Is There a Role For Cytoreductive Drugs For The Concomitant mentioning
confidence: 44%
“…Of note, in this study, hydroxyurea, ruxolitinib, and drug combination did not show an excess risk of hematological second cancer and carcinoma compared with unexposed patients. 80 On the other hand, all of these drugs were associated with an increased risk of nonmelanoma skin cancer. Lastly, a recent Italian study reporting real-world data on 219 MF patients treated with ruxolitinib registered no case of lymphoma development, with a median follow-up after ruxolitinib start matching the median time to lymphoma occurrence reported by Porpaczy and colleagues.…”
Section: Is There a Role For Cytoreductive Drugs For The Concomitanmentioning
confidence: 99%